Gender disparities in red blood cell transfusion in elective surgery: a post hoc multicentre cohort study - Gombotz, H.; Schreier, G.; Neubauer, S.; Kastner, P.; Hofmann, Axel (BM J Group, 2016)
Objectives: A post hoc gender comparison of transfusion-related modifiable risk factors among patients undergoing elective surgery. Settings: 23 Austrian centres randomly selected and stratified by region and level of care. Participants: We consecutively enrolled in total 6530 patients (3465 women and 3065 men); 1491 underwent coronary artery bypass graft (CABG) surgery, 2570 primary unilateral total hip replacement (THR) and 2469 primary unilateral total knee replacement (TKR).Main outcome measures: Primary outcome measures were the number of allogeneic and autologous red blood cell (RBC) units transfused (postoperative day 5 included) and differences in intraoperative and postoperative transfusion rate between men and women. Secondary outcomes included perioperative blood loss in transfused and non-transfused patients, volume of RBCs transfused, perioperative haemoglobin values and circulating red blood volume on postoperative day 5. Results: In all surgical groups, the transfusion rate was significantly higher in women than in men (CABG 81 vs 49%, THR 46 vs 24% and TKR 37 vs 23%). In transfused patients, the absolute blood loss was higher among men in all surgical categories while the relative blood loss was higher among women in the CABG group (52.8 vs 47.8%) but comparable in orthopaedic surgery. The relative RBC volume transfused was significantly higher among women in all categories (CABG 40.0 vs 22.3; TKR 25.2 vs 20.2; THR 26.4 vs 20.8%). On postoperative day 5, the relative haemoglobin values and the relative circulating RBC volume were higher in women in all surgical categories. Conclusions: The higher transfusion rate and volume in women when compared with men in elective surgery can be explained by clinicians applying the same absolute transfusion thresholds irrespective of a patient’s gender. This, together with the common use of a liberal transfusion strategy, leads to further overtransfusion in women.